2021
DOI: 10.3389/fcell.2021.649891
|View full text |Cite
|
Sign up to set email alerts
|

Neurorepair and Regeneration of the Brain: A Decade of Bioscaffolds and Engineered Microtissue

Abstract: Graphical AbstractBioscaffolds potential applications in tissue engineering. Bioscaffolds can be used to grow stem cells and target their differentiation in vitro(upper, left) or be used as stem cell delivery route in a brain injury (upper, right). Bioscaffolds can also contain si/miRNAs that will modify locally neural cells gene expression (lower, left) or contain exosomes/growth factors for paracrine signaling such as stimulating neurogenesis and increase neural stem migration to injury area (lower, right). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 146 publications
0
23
0
1
Order By: Relevance
“…It has been observed that neurons are more prone to thrive when the elastic modulus of a hydrogel is similar to the soft ECM of the brain, whereas astrocytes behave better on stiff substrates [27]. Softer hydrogels induce increased neuronal sprouting as compared to harder hydrogels which lead to neural gliosis [28]. Axonal tips also advance faster on softer hydrogels and appear to retreat from harder areas on a scaffold.…”
Section: Rheological Characterisation Of the Crosslinking Reactionmentioning
confidence: 99%
“…It has been observed that neurons are more prone to thrive when the elastic modulus of a hydrogel is similar to the soft ECM of the brain, whereas astrocytes behave better on stiff substrates [27]. Softer hydrogels induce increased neuronal sprouting as compared to harder hydrogels which lead to neural gliosis [28]. Axonal tips also advance faster on softer hydrogels and appear to retreat from harder areas on a scaffold.…”
Section: Rheological Characterisation Of the Crosslinking Reactionmentioning
confidence: 99%
“…It is imperative to understand that after an external CNS damage or impact, the stimulation and start of neurogenesis is important along with the suppression of the growth-inhibiting processes of the biological response to injury (Urbán and Guillemot, 2014;Zamproni et al, 2021). This process is convoluted and involves various cellular pathways and the bioavailability of the regenerative medicine without extreme invasion is highly required as well as difficult to achieve.…”
Section: Existing Challenges In Neurogenesismentioning
confidence: 99%
“…There is a pressing need for an intervention and introduction of alternate ways to account for more bioavailability of the drugs in the brain without extreme invasive approach in patients. Alternate strategies including bio scaffolds (Zamproni et al, 2021), bioengineering (Oliveira et al, 2018), and nanotechnology (Liaw et al, 2019) have been reported to increase the availability of therapeutics in the CNS and aid neuro repair. Current mediations lack direct stimulation of neurogenesis as they tend to target the stabilization, maturation, and alleviation of neuronal death.…”
Section: Existing Challenges In Neurogenesismentioning
confidence: 99%
“…In this context, a detailed review of the literature highlighting recent achievements and challenges encountered in the development of tissue engineering strategies for brain tissue repair and MRI will be presented. Scaffolds play a key role as a support for cells to anchor and regenerate the injured site of the brain [41]. They need to match the environments from a biochemical and biophysical aspect and stimulate the infiltration of cells.…”
Section: Introductionmentioning
confidence: 99%